Fabrication And Characterization Of Ph-Responsive Poly(Ethylene Glycol) Methyl Ether Methacrylates_Poly(Acrylic Acid) Hydrogel - Salleh, Syahira Amira Mohd (Universiti Sains Malaysia, 2017)
The ionic pH sensitive polymer contains acid groups (carboxylic or sulphonic) or basic groups (ammonium salts) in which response to pH changes in the biological environment. The pH responsive poly(ethylene glycol)/poly(acrylic acid) (PEG/PAA) hydrogel was prepared by using free radical polymerization with a two-step sequential network formation process. The sample prepared are single network of PEG, PAA and hybrid of PEG/PAA hydrogels. The hydrogels were characterized to determine the chemical and mechanical properties as well as the responsive ability of hydrogels towards pH at different pH solution. The Fourier Transform Infrared (FTIR) Spectra showed that PEG/PAA hydrogels synthesized was successfully achieved as C-O-C stretching vibration peak was present. Compression test was used to study the mechanical strength of PEG, PAA and PEG/PAA hydrogels. The mechanical test results showed that the mechanical strength of PEG/PAA hydrogel were considerably greater than the individual polymer network. In addition, the pH responsive behaviour were also studied and it was found that the swelling ratio was increased with the increasing of pH. The result from swelling-deswelling kinetics at pH 3 and pH 7 showed good swelling/deswelling reversibility compared than swelling-deswelling kinetics at pH 10 and pH 7.